The Role of Innovation and New Technologies in Closing the Economic Circuit of Electrical and Electronic Equipment - Vasile Dinu; Giani Ionel Grădinaru; Alin Cristian Maricuț; Bogdan Florin Matei (Amfiteatru Economic)
Digitisation and the circular economy open the possibility to ensure efficient products and services development, while promoting the sustainable development of social well-being. Despite being an area with high potential for adopting business models that integrate the perspective of the two concepts, the electrical and electronic sector depends on the opportunity cost that falls under the constraints on rethinking existing industrial processes to reduce non-reusable waste. Therefore, the present study will show the benefits of moving towards a circular model through innovation and new technologies, in accordance with the connection between digitisation and the circular economy at a territorial level. The results will highlight the particularities of the electrical and electronic equipment and the patterns regarding the approach to integrating the two concepts in the same sector, at the level of the EU bloc states.